2022
DOI: 10.26434/chemrxiv-2022-b3087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Molecule Magnetism in Linear Fe(I) Complexes with Aufbau and non-Aufbau ground-state

Abstract: With the ongoing efforts on synthesizing mono-nuclear single-ion magnets (SIMs) with promising applications in high-density data storage and spintronics devices, the linear Fe(I) complexes emerge as the enticing candidates possessing large unquenched angular momentum. Herein, we have studied five experimentally synthesized linear Fe(I) complexes to uncover the origin of single-molecule magnetic behavior of these complexes. To begin with, we benchmarked our methodology on the experimentally and theoretically we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Yet, an effective spin-reversal barrier height of 226 cm –1 has been reported by Zadrozny et al for a linear two-coordinated iron complex . Subsequently, employing ab initio calculations, we have computed large spin-reversal barriers for the several experimentally synthesized Fe­(I) complexes . Long spin-relaxation times for early 3d or 4f metal complexes have been successfully reported by Ariciu et al Bunting et al have observed a large barrier of 450 cm –1 for a two-coordinated cobalt complex, the highest among SMMs based on 3d metals …”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Yet, an effective spin-reversal barrier height of 226 cm –1 has been reported by Zadrozny et al for a linear two-coordinated iron complex . Subsequently, employing ab initio calculations, we have computed large spin-reversal barriers for the several experimentally synthesized Fe­(I) complexes . Long spin-relaxation times for early 3d or 4f metal complexes have been successfully reported by Ariciu et al Bunting et al have observed a large barrier of 450 cm –1 for a two-coordinated cobalt complex, the highest among SMMs based on 3d metals …”
Section: Introductionsupporting
confidence: 55%
“…27 Subsequently, employing ab initio calculations, we have computed large spin-reversal barriers for the several experimentally synthesized Fe(I) complexes. 34 Long spin-relaxation times for early 3d or 4f metal complexes have been successfully reported by Ariciu et al 35 Bunting et al have observed a large barrier of 450 cm −1 for a twocoordinated cobalt complex, the highest among SMMs based on 3d metals. 36 Among metallocenes of first-row transition elements, ferrocene has gained wide attention due to its ample applications in catalysis, functional materials, and nanotechnology.…”
Section: Introductionmentioning
confidence: 76%
“…Consequently, we have scrutinized the two complexes to investigate their magnetic anisotropy and hence their potential to act as SIMs. The initial version of the manuscript was self-archived in the ChemRxiv repository on February 1, 2022 …”
Section: Introductionmentioning
confidence: 99%
“…27 Hence, it becomes crucial to look into the electronic structure of the system in order to have a comprehensive understanding of the origin of slow relaxation of magnetization. [28][29][30] Into the bargain, Gereka and co-workers have explained the impact of the distortion of the coordination sphere on the slow relaxation for Co II N 6 trigonal prismatic cationic complexes. 31 Hitherto there are many reports available in the published literature regarding poly-coordinated Co(II) complexes yet theoretical work focused on an in-depth study on low-coordinated Co(II) complexes is limited.…”
Section: Introductionmentioning
confidence: 99%